SKAP2 mediates productive neutrophil antimicrobial functions in innate immunity - Nguyen, Giang. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Immunology.; Advisor: Joan Mecsas.; Committee: Stephen Bunnell, David Sykes, Henry Wortis, and John Leong.; Keyword: Immunology.